PSIKOLOGI TOKOH UTAMA DALAM FILM JALAN YANG JAUH, JANGAN LUPA PULANG - Dasilva, Lula; Priyadi, Antonius Totok; Muzammil, Ahmad Rabiul; Seli, Sesilia; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the psychology of the main character in the film Jalan yang Jauh, Jangan Lupa Pulang using Abraham Maslow's humanistic psychology approach. The main issues examined in this research include the fulfillment of physiological needs, safety, love and belonging, self-esteem, and self-actualization experienced by the main character. Additionally, this research aims to develop an Indonesian language teaching module based on the Merdeka Curriculum for Phase F in 11th-grade high school, focusing on drama texts. This study employs a descriptive method with a qualitative research design. The primary data consist of transcripts and film scnes analyzed using humanistic psychology theory. The findings reveal that the main character fulfills their physiological needs, safety, love and belonging, self-esteem gradually, ultimately achieving self-actualization after finding the courage to make a significant life decision. The study also produces an Indonesian language teaching module for 11th-grade high school students, using the film transcript as a learning medium for drama text materials.